AVI Transponder. (1981) - Kamata, Shoichi; Kimura, Yoshinori; Sakuragi, Johji
Abstract : A newly developed AVI transponder is to be used in Automatic Vehicle Identification (AVI) system, which provides identification of moving vehicles passing by a certain location, as to its registration number, and classification etc. This AVI system is characterized by the fact that it utilizes ceramic resonators in the composition of a transponder identification code, and a single microwave carrier to convey an interrogation signal to, and a response signal from, that transponder. The transponder is a completely passive device free of any power supply, and operates as a "Reflector". Overall external dimensions of transponder are 7 × 10 × 1 cm with a weight of 150 grams, the unit is compact, light weight and can be mounted easily on the vehicle, and is easy to carry. All of the circuitry required for the transponder is provided in the form of microstrip lines utilizing MIC (Microwave Integrated Circuit) technology on the PTFE-glass fibre laminate substrate. The transponder circuitry, which consists of printed antenna, microwave modem circuit and medium frequency circuit, is patterned on both surfaces of the single substrate. In this paper, operation principle, circuitry and construction of the transponder will be described.